2021
DOI: 10.3389/fpls.2020.627468
|View full text |Cite
|
Sign up to set email alerts
|

Maize Resistance to Stem Borers Can Be Modulated by Systemic Maize Responses to Long-Term Stem Tunneling

Abstract: Limited attention has been paid to maize (Zea mays L.) resistance induced by corn borer damage, although evidence shows that induced defenses have lower resource allocation costs than constitutive defenses. Maize responses to short- and long-term feeding by the Mediterranean corn borer (MCB, Sesamia nionagrioides) have been previously studied, but the suggested differences between responses could be due to experimental differences. Therefore, in the current study, a direct comparison between short- and long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Those indirect selection approaches were successful for developing maize varieties with increased resistance, probing that hydroxamic content of the leaf-whorl and pith cell-wall strength are important components of resistance to the first and second generations of stem borers, respectively (Russell et al 1975;Barros-Rios et al 2015). Rodriguez et al (2021) recently reported that levels of resistance in the field should depend on induced defense responses of maize plants infested by S. nonagrioides rather than on constitutive resistance levels, evaluating the concentrations of candidate metabolites that may be involved. Therefore, specific methodologies for evaluation of induced plant resistance on stem borer biological performance are needed, as well as the quantification of those potential secondary compounds underlying induced resistance, which could be added as a complementary control method in IPM systems, especially where transgenic Bt hybrids are not allowed or in organic agriculture.…”
Section: Varietal Resistance and Bt Technologymentioning
confidence: 99%
“…Those indirect selection approaches were successful for developing maize varieties with increased resistance, probing that hydroxamic content of the leaf-whorl and pith cell-wall strength are important components of resistance to the first and second generations of stem borers, respectively (Russell et al 1975;Barros-Rios et al 2015). Rodriguez et al (2021) recently reported that levels of resistance in the field should depend on induced defense responses of maize plants infested by S. nonagrioides rather than on constitutive resistance levels, evaluating the concentrations of candidate metabolites that may be involved. Therefore, specific methodologies for evaluation of induced plant resistance on stem borer biological performance are needed, as well as the quantification of those potential secondary compounds underlying induced resistance, which could be added as a complementary control method in IPM systems, especially where transgenic Bt hybrids are not allowed or in organic agriculture.…”
Section: Varietal Resistance and Bt Technologymentioning
confidence: 99%
“…In the course of the evolutionary arms race between plants and pests, plants developed many different defense strategies, including physical defenses to minimize the entry of pathogens like cell wall or spines, and biochemical defenses that can be repulsive or toxic (67). They can be constitutive or induced with different resource allocation costs (53). The setting-up of chemical plant defenses is a paradigm of biological complexity.…”
Section: Introductionmentioning
confidence: 99%